A common structural scaffold in CTD phosphatases that supports distinct catalytic mechanisms. Issue 1 (10th September 2013) - Pons, Tirso; Paramonov, Ida; Boullosa, César; Ibáñez, Kristina; Rojas, Ana M.; Valencia, Alfonso
ABSTRACT The phosphorylation and dephosphorylation of the carboxyl‐terminal domain (CTD) of the largest RNA polymerase II (RNAPII) subunit is a critical regulatory checkpoint for transcription and mRNA processing. This CTD is unique to eukaryotic organisms and it contains multiple tandem‐repeats with the consensus sequence Tyr1–Ser2–Pro3–Thr4–Ser5–Pro6–Ser7. Traditionally, CTD phosphatases that use metal‐ion‐independent (cysteine‐based) and metal‐ion‐assisted (aspartate‐based) catalytic mechanisms have been considered to belong to two independent groups. However, using structural comparisons we have identified a common structural scaffold in these two groups of CTD phosphatases. This common scaffold accommodates different catalytic processes with the same substrate specificity, in this case phospho‐serine/threonine residues flanked by prolines. Furthermore, this scaffold provides a structural connection between two groups of protein tyrosine phosphatases (PTPs): Cys‐based (classes I, II, and III) and Asp‐based (class IV) PTPs. Redundancy in catalytic mechanisms is not infrequent and may arise in specific biological settings. To better understand the activity of the CTD phosphatases, we combined our structural analyses with data on CTD phosphatase expression in different human and mouse tissues. The results suggest that aspartate‐ and cysteine‐based CTD‐dephosphorylation acts in concert during cellular stress, when high levels of reactive oxygen species can inhibit the nucleophilic function of the catalytic cysteine, as occurs in mental and neurodegenerative disorders like schizophrenia, Alzheimer's and Parkinson's diseases. Moreover, these findings have significant implications for the study of the RNAPII‐CTD dephosphorylation in eukaryotes. Proteins 2014; 82:103–118. © 2013 Wiley Periodicals, Inc.